Effect of bran particle size on gastric emptying and small bowel transit in humans: a scintigraphic study. Issue 2 (August 1995) - Vincent, R; Roberts, A; Frier, M; Perkins, A C; MacDonald, I A; Spiller, R C
Abstract : Bran is an effective treatment for constipation but its use is often limited by heartburn and bloating. This study examined the effect of fine and coarse bran (15 g) on the gastric emptying and small bowel transit of a 325 kcal rice test meal. Twelve healthy volunteers underwent a three way cross over study, ingesting the technetium-99m labelled rice meal with or without 15 g of indium-111m labelled fine or coarse bran, in random order. Serial scintigraphic images were obtained to define gastric emptying and colonic arrival of label. Compared with control values (99 (9) minutes) (mean (SEM)), the time to 50% gastric emptying was significantly delayed by coarse but not fine bran, being 121 (6) and 104 (9) minutes respectively, p < 0.05, n = 12. Fundal emptying was unchanged but both brans seemed to increase the proportion of isotope in the antrum at 90 minutes. Small bowel transit was slightly faster with both bran types but in this study the difference was not significant. Both the bran and rice labels moved down the gut without significant separation. Fine bran causes less disturbance of gastric physiology than coarse bran.